Smartphone instrument for portable enzyme-linked immunosorbent assays - Long, Kenneth D. (Biomed Opt Express, 2014)
We demonstrate the utilization of a smartphone camera as a spectrometer that is capable of measuring Enzyme Linked Immunosorbent Assays (ELISA) at biologically-relevant concentrations with the aid of a custom cradle that aligns a diffraction grating and a collimating lens between a light source and the imaging sensor. Two example biomarkers are assayed using conventional ELISA protocols: IL-6, a protein used diagnostically for several types of cancer, and Ara h 1, one of the principle peanut allergens. In addition to the demonstration of limits of detection at medically-relevant concentrations, a screening of various cookies was completed to measure levels of peanut cross-contamination in local bakeries. The results demonstrate the utility of the instrument for quantitatively performing broad classes of homogeneous colorimetric assays, in which the endpoint readout is the color change of a liquid sample.